Distinctive properties of the hepatitis B virus envelope proteins. - Molnar-Kimber, K L (1988)
Using recombinant adenoviral vectors, we expressed and characterized the large, middle, and major envelope proteins of hepatitis B virus (HBV). Cells infected with the recombinant adenovirus which contained the large envelope gene (HS1.HP) expressed predominantly large envelope and small but detectable quantities of middle (4%) and major (6%) envelope proteins in the cell lysate. No HBV envelope proteins were detected in the culture medium from HS1.HP-infected cells. Cells infected with recombinant adenovirus which contained the middle envelope gene (HS2.HP) expressed and secreted the middle and major envelope proteins in a molar ratio of 3:1. Cells infected with the recombinant adenovirus which contained the major envelope gene (HS.HP) expressed and secreted major envelope proteins. The HBV envelope proteins secreted by cells infected with either HS2.HP or HS.HP were assembled in 22-nm particles, as shown by velocity sedimentation rate determination, buoyant densities, and electron microscopy. Cells coinfected with a recombinant adenovirus which contained the large envelope gene and with either HS2.HP or HS.HP expressed similar quantities of the large, middle, and major envelope proteins in the cell lysates. Secretion of the major and middle envelope proteins was inhibited more than 95% by the presence of the large envelope proteins. These results suggest that differential biosynthesis, transport, and processing of the envelope proteins occur during HBV infection, allowing efficient assembly and secretion of virions and hepatitis B surface antigen particles.